Pengaruh Filsafat Iluminasi Dalam Pemikiran Pendidikan Islam - Radinal Mukhtar Harahap (Universitas Islam Negeri Sumatera Utara, 2019)
One of the influential traditions of Islamic education is illumination. His influence stems from the Suhrawardi al-Maqtul with Hikmah al-Isyraq as a base of the foundation. From him, philosophy flourished in Persia, India-Pakistan, Syria, Anatolia, and Europe. His characters in addition to Suhrawardi is Syamsuddin Muhammad al-Syahrazuri, Sa'ad bin Manshur bin Kammunah, Quthb al-Din al-Syirazi, Shadr al-Din Dasytaqi, Ghiyas al-Din Mansur Dasytaki, Jalal al-Din Muhammad bin Sa'ad al-Din al-Dawwami, Mir Muhammad Baqir Damad, Shadr al-Din al-Syirazi or Mulla Sadra, Mulla Hadi Sabziwari, Seyyed Hossein Nasr, Henry Corbin and Sir Muhammad Iqbal. This paper through the library research tracks the influence of illumination in the thinking of Islamic education, which is seen in the concept of science, the methodology of achieving it, consisting of four phases, namely Tazkiyah al-Nafsi, as a stage that indicates that Education needs preparation. The illumination phase and the stage gained unlimited science which suggests that educators are not limited to teachers, but also of Allah and the apostle. The fourth stage is the stage that educators or learners must do, documenting the knowledge that has been taught or studied in written text. Although the illumination comes from various teachings that had evolved before Suhrawardi, this philosophy did not absorb the whole, as Suhrawardi criticized the teaching that became the source of his thinking.